Strategi Pemanfaatan Pantun Dalam Menghasilkan Motif Baju Kaus - Zora, Nofri Duino; Ferdinal, Ferdinal; Syafiola, M.Fedro (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
This research examines the strategy of utilizing Minangkabau pantun in creating T-shirt motifs as an effort to increase the creativity of MSMEs (Micro, Small and Medium Enterprises) in the Gandoriah Beach area, Pariaman City. Using a descriptive qualitative approach, this study analyzes the potential integration of local cultural elements into modern fashion products. The main focus is the creation of rhymes themed on the beauty of Gandoriah Beach that are applied as motifs on T-shirts and tote bags. The proposed strategy includes the creation of short rhymes, selection of attractive color gradations, and aesthetic layout. The main target market is young tourists who visit Gandoriah Beach. The results show that this collaboration between cultural heritage and creative industry has the potential to not only promote local cultural values, but also open up economic opportunities for MSME players. The study concludes that this strategy can be a positive model of local cultural development that contributes to industry growth and community welfare.